Incidence and type of electrolyte abnormalities Iranian children with acute gastroenteritis - Fateme Mosav; Iran Malekzdeh; Mastaneh Moghtaderi (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2020)
Background: Acute Gastroenteritis (AGE) is one of the most common pediatric disorders, causes significant morbidity and is associated with electrolyte imbalances, some of which can be too dangerous. Materials and methods: A prospective cross-sectional study was performed on 473 children admitted to the Children's Medical Center Hospital emergency room for gastroenteritis. These patients received various treatments for gastroenteritis, such as oral rehydration therapy, antiemetic drugs, probiotics and intravenous fluids. The serum electrolyte, urea and creatinine levels of all patients were checked regularly and recorded on the data forms. Results: A total of 437 children participated in this study. Of these, 243 (51%) were men and 231 (49%) women. 4.4% of the patients had mild dehydration, 78.7% had moderate dehydration and 20.8% of the children had severe dehydration. The serum Na range was 116 to 156 mmol / L (mean value 136.61 ± 8.85). The serum potassium level was 3 to 6 mmol / L (mean 4.2 ± 0.64). According to this study, the prevalence of sodium disorders in the study group was 41.6% (4% of severe hyponatraemia with serum Na <120 meq / L, 23.6% with serum Na 120 meq / L at 135 meq / L and 14% hypernatremia with serum Na> 145 meq / L). In our study group there was 17.2% potassium disorder, 13% hypokalaemia (serum K <3.5 mmol / L) and hyperkalaemia 3.7% (serum K> 5.5 mmol / L).